Integrated rice blast disease management under direct drilling and conventional tillage - Silva, Gisele Barata da; Prabhu, Anne Sitarama; Zimmermann, Francisco José Pfeilsticker (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to develop adequate measures for rice blast (Pyricularia grisea) management integrating cultivar resistance, cultural practices and chemical control. Two field experiments were carried out, one under direct drilling and the other one under conventional tillage, during two consecutive rice growing seasons, 1998/1999 and 1999/2000. The treatments totaling 16, in a factorial scheme 24, included two cultivars, Carajás and Primavera, two levels of N, 30 and 60 kg ha-1, non-treated seed and seed treated with pyroquilon, plots non-sprayed and sprayed with two applications of fungicide mixture benomyl and difenoconazole. The incidence and severity of leaf and panicle blast were significantly lower under direct drilling as compared to the conventional tillage. The cultivar Primavera showed greater leaf blast susceptibility, independently of the tillage system. The application of 60 kg ha-1 of N increased leaf blast in the second year. Two applications of fungicide reduced panicle blast severity in both tillage systems. The grain yield under conventional tillage was higher than under direct drilling. The cultivar Carajás was superior to Primavera.